Measurement of the photoelectron-collection efficiency in noble gases and methane - Coelho, L. C. C. (2007)
The photoelectron-collection efficiency from photocathodes in noble gases and methane is experimentally investigated. The ratio between the number of transmitted photoelectrons in the gas media and in vacuum is determined as a function of the applied reduced electric field E/p, where p is the gas pressure. Results are presented for He, Ne, Ar, Xe, Kr and CH4.